2016
DOI: 10.7577/rerm.1823
|View full text |Cite
|
Sign up to set email alerts
|

Plugging into the Umbra: Creative experimentation (in)(on) the boundaries of knowledge production in ECEC research

Abstract: Research into Early Childhood Education and Care (ECEC) policy and practice in the UK Deleuze and Guattari (1987) to explore what form of life might emerge in the smooth space of the umbra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…They open up possibilities for enacting different ways of knowledge making that are geopolitically informed and contest humanist understandings of relations, space, time, bodies, position, and power (Fairchild et al, 2022). Stephanie Springgay and Sarah E. Truman (2018) propose that existing methods need not be refused but that “research methods cannot be framed as a process of gathering data” (p. 204) and I have argued that “ new methods may not be required but what is required is an openness to new ways of activating and thinking methods to explore the flows within and between assemblages” (Fairchild, 2016, p. 26, emphasis in original). It is also important to consider what data are and become in feminist materialist inquiry.…”
Section: Feminist Materialist Inquirymentioning
confidence: 99%
See 1 more Smart Citation
“…They open up possibilities for enacting different ways of knowledge making that are geopolitically informed and contest humanist understandings of relations, space, time, bodies, position, and power (Fairchild et al, 2022). Stephanie Springgay and Sarah E. Truman (2018) propose that existing methods need not be refused but that “research methods cannot be framed as a process of gathering data” (p. 204) and I have argued that “ new methods may not be required but what is required is an openness to new ways of activating and thinking methods to explore the flows within and between assemblages” (Fairchild, 2016, p. 26, emphasis in original). It is also important to consider what data are and become in feminist materialist inquiry.…”
Section: Feminist Materialist Inquirymentioning
confidence: 99%
“…As I have developed my thinking on feminist materialism, I have pondered the idea of time and temporality and what this might mean for qualitative inquiry. I have been thinking with feminist materialism and agential realism for many years and had already been problematizing linearity from a methodological perspective both in Early Childhood Education and Care (ECEC) and in undisciplined and indisciplined inquiry (Fairchild, 2016(Fairchild, , 2021Fairchild et al, 2022). This led me to consider alternative ways to articulate ontic notions of time and temporality and to entangle these with feminist materialist methodologies and theory-praxis.…”
Section: Introduction or Not Maybe This Is An Entry Pointmentioning
confidence: 99%
“…For this reason, we shall be presenting four not-yet data; they are fascinating research situations that, on the one hand, can be found in other professional practices and, on the other hand, require that the researcher lives within this shadow data, moving away from the model of humanist/rational subject and conceiving their subjectivity as emergent. This subjectivity is in a constant flux of connections and entangled with human and non-human materiality (Fairchild, 2016, 2017). We argue that this different view of subjectivity, “one who is in constant flux as connections are made, dropped and remade” (Fairchild, 2017, p. 296), should be embraced not only by qualitative researchers, but also by professionals and managers.…”
Section: Shadow Organizing – Extending the Metaphormentioning
confidence: 99%